Detection of Sensitive Data Leakage for Privacy Preserving - Patil, RJ; Borse, YS (International Journal of Computer Sciences and Engineering, 2025)
According to Risk Base Security, during last few years leakage of sensitive data record has increased. Human mistake is one of the important reason for data exposure. There is an approach in which data is monitored during transmission to detect the inadvertent data leak cause by human mistakes. However it makes the detection process difficult. There is a need of method that support accurate detection without revealing sensitive data. In particular system, Human identity i,e fingerprint is applied to data file for authentication. It is the process in which original fingerprint matrix is compressed using novel down sampling technique. In the technique, original matrix is compressed by calculating arithmetic mean of the sum of the pixel values on each input row matrix to generate a unit input vector for artificial neural network. The fingerprint samples are matched using back propagation technique. The evaluation result shows improved accuracy and detection time.